Enterprise information systems : 20th International Conference, ICEIS 2018, Funchal, Madeira, Portugal, March 21-24, 2018, revised selected papers /: 20th International Conference, ICEIS 2018, Funchal, Madeira, Portugal, March 21-24, 2018, revised selected papers. (2019) - Unknown
No abstract available